2016
DOI: 10.1002/2016gl070093
|View full text |Cite
|
Sign up to set email alerts
|

Distortion and broadening of internal solitary wavefront in the northeastern South China Sea deep basin

Abstract: Internal solitary waves (ISWs) with peculiar fronts are frequently observed in the world ocean by satellite images, though with quite few explanations. In this study a distorted and broadening ISW front across the northeastern South China Sea deep basin is presented by using synthetic aperture radar (SAR) image. To illustrate this peculiar front, a nonlinear refraction model is developed to simulate and evaluate the effects of realistic bottom topography, current, and stratification on its transformation. Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…Table indicates an apparent variation of the wave amplitudes in different transects along the entire wavefront. This result is consistent with those obtained by Xie et al () and by Romeiser and Graber (); both of these previous studies implied that the ISW amplitude could vary greatly along the wavefront around the DSA. At transect N2 (located at 20.89°N, 116.9°E), the SAR‐derived wave amplitude of −94.53 m is comparable to the simulated amplitudes of −130 and −80 m along the tracks of ∼20.8°N and ∼21.5°N at east of 117°E calculated in Xie et al ().…”
Section: Numerical Simulations Of Isw Refraction and Reconnection Behsupporting
confidence: 93%
See 1 more Smart Citation
“…Table indicates an apparent variation of the wave amplitudes in different transects along the entire wavefront. This result is consistent with those obtained by Xie et al () and by Romeiser and Graber (); both of these previous studies implied that the ISW amplitude could vary greatly along the wavefront around the DSA. At transect N2 (located at 20.89°N, 116.9°E), the SAR‐derived wave amplitude of −94.53 m is comparable to the simulated amplitudes of −130 and −80 m along the tracks of ∼20.8°N and ∼21.5°N at east of 117°E calculated in Xie et al ().…”
Section: Numerical Simulations Of Isw Refraction and Reconnection Behsupporting
confidence: 93%
“…This result is consistent with those obtained by Xie et al () and by Romeiser and Graber (); both of these previous studies implied that the ISW amplitude could vary greatly along the wavefront around the DSA. At transect N2 (located at 20.89°N, 116.9°E), the SAR‐derived wave amplitude of −94.53 m is comparable to the simulated amplitudes of −130 and −80 m along the tracks of ∼20.8°N and ∼21.5°N at east of 117°E calculated in Xie et al (). Therefore, referring to the amplitude variations in Table and assuming the wave amplitude is −130 m at ∼20.8°N near the DSA, we set the initial amplitudes of the five ISWs from north to south in the northern ISW branch as −60, −60, −60, −130, and −100 m, and the other six ISWs from north to south in the southern ISW branch as −5, −5, −10, −15, −25, and −40 m.…”
Section: Numerical Simulations Of Isw Refraction and Reconnection Behsupporting
confidence: 93%
“…This study reports the statistical characteristics and spatial‐temporal variation in the Sulu Sea eddies for the first time. Because internal waves and solitons are frequent in the Sulu Sea and eddies are important to the propagation and evolvement of internal waves (Dunphy & Lamb, ; Ponte & Klein, ) and solitons (Xie et al, ), these results can be used for further studies of those dynamic processes. We also proposed two mechanisms of eddy generation in the Sulu Sea.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The polarity conversion of mode-1 ISW in the northern SCS can be well demonstrated by adopting the Korteweg-de Vries (KdV)-type equations (Cai et al, 2002;Liu et al, 1998;Orr & Mignerey, 2003). A hindcast numerical simulation by Shen et al (2009) reproduced the nonlinear transformation of ISWs from symmetrical to severely deformed waveform as observed, and they showed that the APE might begin to exceed the KE at the depth around 250-350 m. The recent theoretical and/or numerical simulations (e.g., Grimshaw et al, 2014;Lamb & Warn-Varnas, 2015;Liao et al, 2014;Xie, He, et al, 2015;Xie et al, 2016) further show that the shoaling dynamics of mode-1 ISWs in the northern SCS are quite sensitive to the topography, rotation, background stratification and current, initial water depth, and so forth. For instance, due to the combined effect of rotation and topography, Grimshaw et al (2014) show the formation of secondary trailing ISW packet associated with the radiated inertia-gravity waves from the leading mode-1 ISW.…”
Section: Introductionmentioning
confidence: 86%
“…Lamb and Warn‐Varnas () show that the shoaling ISWs initialized at depths of 1 and 3 km, respectively, exhibit significant differences and thus suggest the importance of including the transbasin evolution in simulating the shoaling dynamics of ISWs in the northern SCS. Xie et al () reported the distortion and broadening of long ISW front observed by the synthetic aperture radar image and showed that it was due to the effects of strong background mesoscale current and variable bottom topography, respectively, in the deep basin region.…”
Section: Introductionmentioning
confidence: 99%